The pH Value as a Factor Modifying Bacterial Colonization of Sinonasal Mucosa in Healthy Persons. (September 2019) - Morawska-Kochman, Monika; Jermakow, Katarzyna; Nelke, Kamil; Zub, Krzysztof; Pawlak, Wojciech; Dudek, Krzysztof; Bochnia, Marek
Objective: The aim of the present study is to determine and compare the range of pH value in nasal and sinus cavities in vivo regarding the presence of bacteria colonizing sinonasal mucosa among healthy subjects. Methods: The nasal pH value measurement using a portable pH meter (Dx-pH System, Restech) and the microbiological culture swab were taken from beneath the middle turbinate and in the sinus cavity in 39 healthy subjects during maxillary bone corrective osteotomy with the Le Fort I technique. Results: The mean pH value (independently of sex, P = .441) in the healthy sinus cavity was statistically higher than in the nasal middle meatus: 7.96 (SD ± 0.29) versus 7.83 (SD ± 0.30) ( P = .032). Forty-eight strains of bacteria were cultured from sinus maxillaries cavities—aerobic 36.8%, aerobic and anaerobic 52.6%, anaerobic only 10.5%—and 23 strains from the nasal meatus—aerobic 25%, aerobic and anaerobic 75%. A statistically significant correlation was found between the type and location of 8 microorganisms, especially Propionibacterium acnes, identified only in the sinus cavities. Conclusions: Differences in the pH value between the middle nasal meatus and the maxillary sinus are characteristic of healthy subjects and could be associated with the diverse bacterial flora. The role of bacteria Propionibacterium acnes seems to be crucial for the pH range and sinus flora in healthy subjects.